1997
DOI: 10.1073/pnas.94.22.12133
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged production of NADPH oxidase-corrected granulocytes after gene therapy of chronic granulomatous disease

Abstract: Little is known about the potential for engraftment of autologous hematopoietic stem cells in human adults not subjected to myeloablative conditioning regimens. Five adult patients with the p47 phox deficiency form of chronic granulomatous disease received intravenous infusions of autologous CD34 ؉ peripheral blood stem cells (PBSCs) that had been transduced ex vivo with a recombinant retrovirus encoding normal p47 phox . Although marrow conditioning was not given, functionally corrected granulocytes were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(163 citation statements)
references
References 32 publications
3
153
0
7
Order By: Relevance
“…39,40 This would be desirable in the genetic therapy of congenital non-malignant disorders such as Gaucher disease or chronic granulomatous disease. 41,42 Materials and methods Mice All mice were purchased from the Jackson Laboratories (Bar Harbor, ME, USA). Female C57BL/6J (homozygous for the single ␤-hemoglobin haplotype) mice were used as bone marrow donors.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 This would be desirable in the genetic therapy of congenital non-malignant disorders such as Gaucher disease or chronic granulomatous disease. 41,42 Materials and methods Mice All mice were purchased from the Jackson Laboratories (Bar Harbor, ME, USA). Female C57BL/6J (homozygous for the single ␤-hemoglobin haplotype) mice were used as bone marrow donors.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed transient restoration of low levels of oxidase activity detectable in 0.06% to 0.2% of peripheral blood neutrophils. 58 These data suggest that gene therapy protocols for CGD and other PIs in which there is no physiologic selective advantage for corrected cells will need either myeloablation, more efficient gene transduction, or both to generate a large enough proportion of corrected cells to be clinically beneficial.…”
Section: Cgdmentioning
confidence: 99%
“…The first phase I/II gene therapy trials for CGD were conducted in the United States almost 11 years ago. [31][32][33] Although the level of correction achieved was low (0.004-0.6% functionally corrected cells), they provided clear evidence that a gene therapy approach for CGD was feasible and paved the way for further clinical trials. One common feature of these initial trials was the lack of bone marrow conditioning to enhance engraftment of transduced HSCs.…”
Section: Gene Therapy and Clinical Trials (Part I) E Altonmentioning
confidence: 99%